Antibiotic resistance and plasmid profiling of Vibrio parahaemolyticus isolated from cockles in Padang, Indonesia - Yusop, Zulkifli; Mohammed Alitheen, Noorjahan Banu; Abdul Rahim, Raha; Yeap, Swee Keong; Marlina; Radu, Son; Nishibuchi, Mitsuaki (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
Vibrio parahaemolyticus is one of the most widely recognized pathogenic Vibrio species due to numerous outbreaks and its’ wide occurrence in marine environment. In this study, 32 isolates of V. parahaemolyticus isolated from cockles were tested for sensitivity to 16 antibiotics and the presence of plasmids. All the isolates were multi-resistance, defined as resistant to at least three different antibiotics with multiple antibiotic resistance indexes ranging from 0.31 to 0.69, indicating the isolates originate from high risk sources of contamination where antibiotics are often used. In the plasmid profiling test, only 15 isolates (47%) harbored plasmid DNA, which ranged in size from 2.7 to 56.2 kb, separating the isolates into 14 plasmid profiles. Hence, food contaminated with antibiotic resistant V. parahaemolyticus could be a major threat to public health due to the distinct possibility that they can be a significant reservoir of genes encoding antibiotic resistance determinants that can be transferred intra or interspecies. As in many developing countries, raw food hygiene and antimicrobial resistance epidemiology is still in the infancy stage in the locality of the study and thus our data provide a current baseline profile of antimicrobial resistance and plasmid of V. parahaemolyticus from cockles in Padang, Indonesia.